Venous graft-derived cells participate in peripheral nerve regeneration. - Mitra Lavasani; Sebastian Gehrmann; Burhan Gharaibeh; Katherine A Clark; Robert A Kaufmann; Bruno Péault; Robert J Goitz; Johnny Huard (PLoS ONE)
Background Based on growing evidence that some adult multipotent cells necessary for tissue regeneration reside in the walls of blood vessels and the clinical success of vein wrapping for functional repair of nerve damage, we hypothesized that the repair of nerves via vein wrapping is mediated by cells migrating from the implanted venous grafts into the nerve bundle. Methodology/principal findings To test the hypothesis, severed femoral nerves of rats were grafted with venous grafts from animals of the opposite sex. Nerve regeneration was impaired when decellularized or irradiated venous grafts were used in comparison to untreated grafts, supporting the involvement of venous graft-derived cells in peripheral nerve repair. Donor cells bearing Y chromosomes integrated into the area of the host injured nerve and participated in remyelination and nerve regeneration. The regenerated nerve exhibited proper axonal myelination, and expressed neuronal and glial cell markers. Conclusions/significance These novel findings identify the mechanism by which vein wrapping promotes nerve regeneration.